Method for manufacturing electrode, electrode, and battery
Patent Information
- Application Number
- JP2023130509
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-09
AI Technical Summary
【0007】 本開示の一実施形態によれば、液系電池に適用した場合のセル容量に優れる電極の製造方法、液系電池に適用した場合のセル容量に優れる電極、及びこの電極を含む電池が提供される。
Smart Images

Figure 2025025611000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing an electrode, an electrode, and a battery. [Background technology]
[0002] 2. Description of the Related Art Batteries such as lithium ion secondary batteries use electrodes in which active material particles are fixed to the surface of a current collector such as a metal foil with a binder. Known methods for manufacturing electrodes include a method (also called a wet method) in which a composition made by mixing active material particles and a binder with a solvent is applied to the surface of a current collector, and a method (also called a dry method) in which active material particles are fixed to a current collector with a binder without using a solvent.
[0003] As a method for manufacturing an electrode by a dry method, a method has been proposed in which a resin that has the property of being fibrillated when a shear force is applied is used as a binder. For example, Patent Document 1 describes a method in which PTFE in a mixture containing active material particles and polytetrafluoroethylene (PTFE) is fibrillated to produce an electrode film, and then this electrode film is integrated with a current collector to manufacture an electrode. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2022-3694 A Summary of the Invention [Problem to be solved by the invention]
[0005] The electrode obtained by the method described in Patent Document 1 has room for improvement in cell capacity when applied to a battery that uses an electrolyte (also called a liquid battery). An object of the present invention is to provide a method for manufacturing an electrode having excellent cell capacity when applied to a liquid battery, an electrode having excellent cell capacity when applied to a liquid battery, and a battery including this electrode. [Means for solving the problem]
[0006] Means for solving the above problems include the following embodiments. <1> 1. A method for producing an electrode for use in a battery containing an electrolyte, comprising: coating at least a portion of the surface of the carbon particles with a resin; mixing the resin-coated carbon particles with polytetrafluoroethylene to obtain a mixture; and converting the polytetrafluoroethylene in the mixture into fibers. <2> The resin coverage of the carbon particles is 3% or more. <1> A method for producing the electrode according to claim 1. <3> 1. An electrode for use in a battery containing an electrolyte, comprising: A current collector and an electrode layer are included. The electrode layer includes carbon particles at least a portion of whose surface is coated with a resin, and fibrous polytetrafluoroethylene. <4> The resin coverage of the carbon particles is 3% or more. <3> The electrode according to claim 1. <5> <3> or <4> A battery comprising the electrode according to claim 1 and an electrolyte. Effect of the Invention
[0007] According to one embodiment of the present disclosure, there is provided a manufacturing method for an electrode having excellent cell capacity when applied to a liquid battery, an electrode having excellent cell capacity when applied to a liquid battery, and a battery including this electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified.
[0009] <Electrode manufacturing method> The method for producing an electrode according to the present disclosure includes: 1. A method for producing an electrode for use in a battery containing an electrolyte, comprising: coating at least a portion of the surface of the carbon particles with a resin; mixing the resin-coated carbon particles with polytetrafluoroethylene to obtain a mixture; and converting the polytetrafluoroethylene in the mixture into fibers.
[0010] The electrode manufactured by the method of the present disclosure exhibits superior cell capacity when applied to a liquid battery, compared to an electrode formed from a mixture obtained by mixing carbon particles not coated with a resin with PTFE. The reason for this is believed to be, for example, as follows. Electrodes made by fiberizing PTFE, which is contained as a binder together with carbon particles, have a smaller contact area between the carbon particles and the binder and a larger area of exposed surface of the carbon particles than electrodes made by other methods (wet method, electrostatic method, etc.). For this reason, a relatively large amount of a coating called SEI (Solid Electrolyte Interface) is formed on the surface of the carbon particles during the initial charge and discharge of the battery. While the SEI has functions such as suppressing the decomposition of the electrolyte, excessive formation of the SEI leads to an increase in irreversible capacity (i.e., a decrease in cell capacity) due to the fixation of lithium ions. In the method of the present disclosure, an electrode is manufactured using carbon particles at least partly coated with a resin, which suppresses excessive formation of SEI on the surface of the carbon particles and maintains sufficient cell capacity.
[0011] According to the method of the present disclosure, an electrode can be produced without using a solvent, which is advantageous in terms of reducing the production cost of the electrode and reducing the impact on the environment and living organisms.
[0012] Hereinafter, the process of coating at least a portion of the surface of the carbon particles with resin will also be referred to as "process 1," the process of mixing the resin-coated carbon particles with PTFE to obtain a mixture will also be referred to as "process 2," and the process of fiberizing the PTFE in the mixture will also be referred to as "process 3."
[0013] (Process 1) In step 1, at least a portion of the surface of the carbon particles is coated with a resin. The type of carbon particles used in this step is not particularly limited, and can be selected from materials commonly used as negative electrode active materials.
[0014] Specific examples of the material of the carbon particles include graphite, soft carbon, hard carbon, etc. The carbon particles may be secondary particles formed by aggregating a plurality of primary particles. The carbon particles used in the manufacture of the electrode may be of one type alone or two or more types. The volume average particle size of the carbon particles is not particularly limited and can be selected, for example, within the range of 5 μm to 30 μm.
[0015] In the present disclosure, the volume average particle size of particles is the value (D50) at which the cumulative amount from the small diameter side reaches 50% in the volume-based particle size distribution measured by a laser diffraction / scattering method.
[0016] The type of resin used to coat the carbon particles in this step is not particularly limited, and can be selected from materials commonly used in the manufacture of batteries. Specific examples of the resin include polyvinylidene fluoride, polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylate, and polymethacrylate. The resin used in this step may be one type alone or two or more types. From the viewpoints of adhesive strength, affinity with PTFE, resistance to electrolyte, etc., the resin is preferably polyvinylidene fluoride (PVdF).
[0017] From the viewpoint of ensuring a sufficient cell capacity, the coverage of the surfaces of the carbon particles with the resin is preferably 3% or more, more preferably 5% or more, and even more preferably 10% or more. The coverage of the surface of the carbon particles with the resin may be 60% or less, 50% or less, or 40% or less.
[0018] The coverage of the surface of the carbon particles with the resin is measured by an image analysis method. As an image analysis method, for example, F mapping is performed by EDX (energy dispersive X-ray spectroscopy). Specifically, carbon particles covered with resin are observed by SEM (scanning electron microscope), and F mapping is performed by EDX. Regions X corresponding to the carbon particles and regions Y in region X where resin (F) exists are binarized, and the coverage is calculated by the following formula. Coverage rate (%) = (Y area / X area) x 100
[0019] In this step, the method for coating at least a part of the surface of the carbon particles with a resin is not particularly limited, and can be carried out by a known method. For example, a composite treatment may be carried out in which carbon particles and a resin are kneaded in a mixer or the like to coat at least a part of the surface of the carbon particles with the resin. The amount of resin relative to 100 parts by mass of carbon particles can be selected, for example, within the range of 1 part by mass to 20 parts by mass, or 2 parts by mass to 10 parts by mass.
[0020] (Process 2) In step 2, the resin-coated carbon particles and PTFE are mixed to obtain a mixture. The mixing method is not particularly limited, and can be carried out using known means. The amount of PTFE relative to 100 parts by mass of the carbon particles in the mixture can be selected, for example, within the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass.
[0021] The PTFE that is mixed with the carbon particles in step 2 may be in particulate form. The mixture obtained in step 2 may not contain a solvent. In step 2, at least a portion of the PTFE may be fibrous, or a granule may be produced in which the carbon particles are bound by the fibrous PTFE.
[0022] The mixture of resin-coated carbon particles and PTFE may contain a binder other than PTFE. The binder other than PTFE may be selected from the resins for coating carbon particles described above. When the mixture contains a binder other than PTFE, the content thereof may be 20 parts by mass or less, 10 parts by mass or less, or 5% by mass or less relative to 100 parts by mass of PTFE.
[0023] The mixture of the resin-coated carbon particles and PTFE may contain a conductive material, specifically, carbon materials such as carbon black (acetylene black, thermal black, furnace black, etc.) and carbon nanotubes. When the mixture contains a conductive material, the content thereof can be selected from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass, relative to 100 parts by mass of the carbon particles.
[0024] (Step 3) In step 3, the PTFE in the mixture obtained in step 2 is fiberized. The method for converting PTFE into fibers is not particularly limited, and can be carried out by using known means. From the viewpoint of workability when integrating the mixture after fiberizing PEFE with the current collector, it is preferable to fiberize PTFE and mold the mixture into a sheet in step 3. As a method for converting PTFE into fibers and forming the mixture into a sheet, for example, a rolling treatment using a roll press machine can be mentioned.
[0025] The thickness of the molded product obtained by forming the mixture into a sheet is not particularly limited and can be adjusted according to the desired thickness of the electrode layer. For example, the thickness of the molded product can be selected in the range of 10 μm to 200 μm.
[0026] The mixture obtained after fiberizing PTFE in step 3, preferably a sheet-like molded product, is integrated with a current collector to form an electrode. The method for integrating the mixture obtained by fiberizing PTFE with the current collector is not particularly limited, and can be carried out by using a known means. For example, the mixture and the current collector may be pressure-bonded using a roll press, a plate press, or the like. The material of the current collector is not particularly limited, and can be selected from known materials such as aluminum, copper, nickel, titanium, and stainless steel.
[0027] <Electrode> The electrode of the present disclosure comprises: 1. An electrode for use in a battery containing an electrolyte, comprising: A current collector and an electrode layer are included. The electrode layer is an electrode including carbon particles at least partly coated with a resin on the surface thereof, and fibrous polytetrafluoroethylene (PTFE fiber).
[0028] The electrodes of the present disclosure exhibit superior cell capacity compared to electrodes containing carbon particles and PTFE fibers that are not surface-coated with a resin.
[0029] The details and preferred aspects of the electrode and each material contained in the electrode of the present disclosure are the same as the details and preferred aspects of the electrode manufactured by the above-mentioned electrode manufacturing method and each material used therein.
[0030] The electrode of the present disclosure may further include a member other than the current collector and the electrode layer including the active material particles and the PTFE fibers. For example, the electrode of the present disclosure may further include an electrode layer that does not include the PTFE fibers.
[0031] <Battery> The battery of the present disclosure includes the electrode of the present disclosure described above and an electrolyte solution. The battery of the present disclosure includes the electrode of the present disclosure as the negative electrode.
[0032] The type of electrolyte contained in the battery is not particularly limited, and can be selected from electrolytes commonly used in liquid batteries.
[0033] The type of battery disclosed herein is not particularly limited, and can be selected from batteries such as a lithium ion secondary battery, a lead storage battery, a nickel-metal hydride battery, a nickel-cadmium storage battery, a nickel-iron storage battery, a nickel-zinc storage battery, a silver oxide-zinc storage battery, a cobalt titanium lithium secondary battery, and a sodium ion secondary battery. EXAMPLES
[0034] The present disclosure will be described in more detail below with reference to examples, but the invention of the present disclosure is not limited to these examples.
[0035] <Example: Preparation of negative electrode> The materials listed below were charged into an MP mixer (Nippon Coke & Engineering Co., Ltd.) in the amounts shown in Table 1, and a composite treatment was carried out at 10,000 rpm for 10 minutes to coat the surfaces of the carbon particles with resin. Carbon particles: graphite (volume average particle size: 20 μm) Resin: PVDF
[0036] After the composite treatment, PTFE was further added to the MP mixer and mixed at 300 rpm for 180 seconds, followed by further mixing at 5,000 rpm for 500 seconds to form granules in which the carbon particles were bound by the fibrous PTFE.
[0037] The mixture containing the granules was rolled (linear pressure: 0.4 t / cm) using a roll press machine to convert the PTFE into fibers and form them into a sheet (thickness: 200 μm). The sheet-like molded body and copper foil (thickness: 8 μm) serving as a current collector were bonded together using a flat press (load: 5 t, 160° C.).
[0038] Through the above steps, a negative electrode was obtained in which a negative electrode layer including carbon particles at least partially coated with a resin and PTFE fibers was disposed on a current collector.
[0039] <Comparative Example: Preparation of Negative Electrode> A negative electrode was produced in the same manner as in Example 1, except that the composite treatment of the carbon particles was not carried out.
[0040] <Evaluation of coverage> The carbon particles after the composite treatment were observed under SEM, and F mapping was performed using an EDX attached to the SEM to calculate the coverage of the carbon particles with the resin. The results are shown in Table 1.
[0041] <Cell capacity evaluation> A small cell was produced using the negative electrode produced in the examples and comparative examples and the positive electrode produced by the following method. A mixed solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate (EC:DMC:EMC=30:34:36, vol%) containing 1.14M LiPF6 was used as the electrolyte. The discharge capacity of the small cell thus fabricated was measured by the following method. The results are shown in Table 1. Measurement method: Perform CCCV (cut current: 1 / 20C) at a current value of 0.3C in the range of 4.25V to 2.5V, and calculate the discharge capacity (mAh / g).
[0042] (Preparation of positive electrode) A paste containing NCM (97.5 parts by mass) as a positive electrode active material, acetylene black (1.5 parts by mass) as a conductive material, and PVdF (1 part by mass) as a binder was applied onto aluminum foil (thickness: 12 μm) as a current collector to prepare a positive electrode.
[0043] [Table 1]
[0044] As shown in Table 1, the positive electrode of the embodiment made from carbon particles at least partially coated with resin and PTFE has a larger cell capacity than the positive electrode of the comparative example made from carbon particles not coated with resin and PTFE. The above results suggest that coating the surfaces of carbon particles with resin suppresses the excessive formation of SEI on the surfaces of carbon particles, contributing to an increase in cell capacity.
Claims
1. 1. A method for producing an electrode for use in a battery containing an electrolyte, comprising: coating at least a portion of the surface of the carbon particles with a resin; mixing the resin-coated carbon particles with polytetrafluoroethylene to obtain a mixture; and converting the polytetrafluoroethylene in the mixture into fibers.
2. The method for producing an electrode according to claim 1 , wherein the resin covers at least 3% of the carbon particles.
3. 1. An electrode for use in a battery containing an electrolyte, comprising: A current collector and an electrode layer are included. The electrode layer includes carbon particles at least a portion of whose surface is coated with a resin, and fibrous polytetrafluoroethylene.
4. 4. The electrode according to claim 3, wherein the resin covers at least 3% of the carbon particles.
5. A battery comprising the electrode according to claim 3 or 4 and an electrolyte solution.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP1999120992A
Carbon material, negative electrode for secondary lithium ion battery, and secondary lithium ion battery
JP2002117851A
Carbon material for nonaqueous electrolyte secondary battery, anode material, and nonaqueous electrolyte secondary battery
JP2011210461A
Negative electrode for lithium ion secondary battery and for lithium ion capacitor
JP2015156293A
Manufacturing method of positive electrode for lithium secondary battery, positive electrode for lithium secondary battery, and agglomerated material
JP2015170550A